Implementation of the Authority of the Ombudsman of the Republic of Indonesia Representative Office in East Java in Handling Maladministration: Qualitative Study and Analysis of State Administrative Law - Yasin, Fikri; Taufiqurokhman; Beni Pramula; Evi Satispi (Jurisprudentie: Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2025)
This study aims to evaluate the performance of the Ombudsman of the Republic of Indonesia Representative Office in East Java in resolving reports of maladministration in public services. The research focuses on the effectiveness of the Ombudsman's authority based on Law Number 37 of 2008 concerning the Ombudsman of the Republic of Indonesia, Law Number 25 of 2009 concerning Public Services, and the general principles of good governance (AUPB). The method used is legal research with a qualitative approach, through document analysis, in-depth interviews, and observation of the report resolution process. The results of the study show that the East Java Ombudsman has carried out its external oversight function quite effectively, particularly in verifying reports, clarifying with the reported agencies, and issuing recommendations. However, several obstacles were still found, such as limited resources, low levels of compliance by agencies with Ombudsman recommendations, and suboptimal coordination between agencies. This study confirms that the effectiveness of the Ombudsman is largely determined by the alignment between the legal framework, institutional capacity, and the legal culture of public service providers. The findings of this study are expected to serve as a basis for improving public service oversight policies and strengthening the position of the Ombudsman in the state administrative legal system.